Processing and characterization of ultra-high temperature ceramic matrix composites via water based slurry impregnation and polymer infiltration and pyrolysis. Issue 1 (1st January 2023) - Servadei, Francesca; Zoli, Luca; Galizia, Pietro; Piancastelli, Andreana; Sciti, Diletta
Abstract: Uncoated PAN-based carbon fibre-reinforced ultra-high temperature ceramic matrix composites via aqueous ZrB2 powder-based slurry impregnation coupled with mild polymer infiltration and pyrolysis, using allylhydrido polycarbosilane as source of amorphous SiC(O), were manufactured. To demonstrate the versatility of the process to realize tailored materials, unidirectional (UD), two dimensional (2D) and needle-punched (2.5D) cloths were impregnated. Microstructure and mechanical properties were investigated and correlated with fibre properties and architecture. The flexural strength was found over 250 MPa for unidirectional reinforced material, while the modulus exceeded 250 GPa for needle-punched one. The homogeneous distribution of UHTC phase around each single fibre and the weak fibre/matrix interface, due to the mild pyrolysis conditions, are the hallmark of this process and the key to improve durability and performance of materials for extreme environments without the application of expensive coating on fibres.